Flipped Classroom and DICT on K-12 Education: Systematic review and proposal (Research, Society and Development, 2020)
In face of the constant social changes brought by technology, the educational sector is in need of innovation. As much as the Digital Information and Communication Technologies (DICT) dictate these changes, they are not present in education in a significant manner. The Active Methodologies, especially if combined with the DICT, have the potential of transforming teaching and learning. Facing this scenario, this paper presents a systematic literature review about the Flipped Classroom Methodology (FCM) focusing on K-12 education, as well as a model proposal for the use of DICT as a supporting tool for the FCM. The results show that the research about FCM is not sufficiently explored in practice.